Genetic and phenotypic features defining industrial relevant Lactococcus lactis, L. cremoris and L. lactis biovar. diacetylactis strains - Torres Manno, Mariano Alberto (2018)
Lactococcus lactis strains constitute one of the most important starter cultures for cheese production. In this study, a genome-wide analysis was performed including 68 available genomes of L. lactis group strains showing the existence of two species (L. lactis and L. cremoris) and two biovars (L. lactis biovar. diacetylactis and L. cremoris biovar. lactis). The proposed classification scheme revealed coherency among phenotypic (through in silico and in vivo bacterial function profiling), phylogenomic (through maximum likelihood trees) and genomic (using overall genome sequence-based parameters) approaches. Strain biodiversity for the industrial biovar. diacetylactis was also analyzed, finding they are formed by at least three variants with the CC1 clonal complex as the only one distributed worldwide. These findings and methodologies will help improve the selection of L. lactis group strains for industrial use as well as facilitate the interpretation of previous or future research studies on this diverse group of bacteria.